The role of expectations for currency crisis dynamics - The case of the Turkish lira - Joscha Beckmann; Robert L. Czudaj (Journal of Forecasting, 2023)
This paper examines whether and how expectations have contributed to the turbulent path of the Turkish lira since 2008. We derive uncertainty measures surrounding gross domestic product (GDP) growth, inflation, the interest rate, and exchange rates based on survey data from Consensus Economics. Our results illustrate that forecasts have affected realized exchange rates and stock market returns via increased uncertainty. We also show that expectations regarding monetary policy have changed throughout the sample period. In line with, a gradual adjustment of expectations professionals have accounted for the violation of the Taylor rule.
Keywords: 330; disagreement; expectations; foreign exchange; survey data; Taylor rule; Turkish lira; uncertainty